THE ROLE OF THE VILLAGE GOVERNMENT IN THE DEVELOPMENT OF MANGO ISLAND TOURISM IN SIBALUTON VILLAGE, BASIDONDO DISTRICT, TOLITOLI REGENCY - Rajamuda, Moh. Ajrin; Irvan, Muhammad; Yanto, Edi (International Journal of Economic Entrepreneurship and Business Management, 2024)
This study aims to find out what are the Roles of the Village Government in the Development of Mango Island Tourism in Sibaluton Village. This study uses a qualitative descriptive method, namely collecting data in the form of words or pictures so that it does not emphasize the number of data collected after being analyzed and then descriptive so that it is easy to be understood by others. The results of the research were obtained that the role of the village government and the strategy for the development of mango island tourism has been running well, the Sibaluton village government has coordinated with the people of Sibaluton regarding mango island tourism and invited the local community to participate in the development of mango island tourism by fulfilling tourist facilities and assisting in the construction of various tourist infrastructures. In addition, the village government also provides innovations to the community to take advantage of the existence of mango island to get income by facilitating crossing tools used by visitors to get to tourist attractions, and also the Sibaluton village government provides infrastructure facilities on mango island.Keywords: The Role of the Government; Village Government; Development; Tour; Island Tourism